Uji AKTIVITAS ANTIBAKTERI EKSTRAK ETANOL DAUN KEMUNING (Murraya paniculata (L.) Jack) TERHADAP BAKTERI Streptococcus pneumoniae - El Santi Sadida; Na’imatul Retno Faizah; Octaviana Dyah Oentari (Ar-Rasyid: Jurnal Publikasi Penelitian Ilmiah, 2025)
One of the main infectious causes of death in Indonesia is pneumonia, or inflammation of the lungs, which is brought on by a number of germs, including the bacteria Streptococcus pneumoniae. The objective of this study is to ascertain the ideal concentration at which antibacterial activity is present and to assess the antibacterial activity of ethanol extracts of kemuning leaves (Murraya paniculata (L.) Jack) against Streptococcus pneumoniae at concentrations of 15%, 20%, and 25%. The disc diffusion method was used to perform the antibacterial test after kemuning leaves were extracted using the maceration procedure with 70% ethanol.  One-way ANOVA was used to analyse the data.  With the highest inhibition zone at a concentration of 25% (10.31 ± 0.58 mm), classed as strong, and concentrations of 15% (9.83 ± 0.39 mm) and 20% (9.64 ± 0.73 mm) classified as moderate, the results demonstrated that the ethanol extract of kemuning leaves exhibited significant antibacterial activity.  The one-way ANOVA test results indicated that the concentrations differed significantly (p < 0,05).  According to this study, kemuning leaf extract has the potential to be an antibacterial agent against Streptococcus pneumoniae.